Basement reactivation and structural inheritance in the Jurassic to Neogene evolution of the North Patagonian Andes (41° 08’ – 41° 11’ S), Argentina - Peltzer Conti, Sofía (2024)
Structural inheritance is a major control on the Andean structural architecture and magma emplacement, particularly in Patagonia, where the genesis of sedimentary basins and magmatic arcs has been largely influenced by basement fabrics. Based on new geologic, structural, microstructural and geochronologic data, the aim of this contribution is to evaluate the influence of pre-existing mechanical anisotropies of the Paleozoic basement on the Jurassic-Neogene tectonic evolution in the Paso de las Nubes area (North Patagonian Andes, Argentina). U-Pb zircon data of an orthogneiss yielded an age of 166 ± 2 Ma, which is consistent with the Jurassic batholith reported in the North Patagonian Andes, being thus coeval with retrograde metamorphism and deformation in the metasedimentary wallrock. Fault kinematic data indicate a Jurassic transtensional regime, strongly controlled by basement reactivation. On the other hand, a second kinematic population records a mainly strikeslip solution, associated with partitioned Neogene transpression.